In Silico Studies: Stigmastan-3,6-dione in the Ethyl Acetate Fraction of Momordica charantia L Fruit has immunostimulant and anti-inflammatory activity - Rachmi Ridho; Bambang Pontjo Priosoeryanto; Esti Mumpuni; Andri Prasetiyo; Syamsudin Abdillah (Journal of Natural Product for Degenerative Diseases, 2024)
Momordica charantia L fruit provides an immunomodulatory effect by stimulating certain components of the body's immune system. Bioactive phytochemicals from M. charantia L function as anti-inflammatory agents by reducing levels of pro-inflammatory cytokine secretion including IL-1, IL-6, IL-8, TNF-α, NF-kB. This research looks at the insilico mechanism of action of the active ingredient of the EtOAc fraction of M. charantia L fruit as an immunostimulant and anti-inflammatory. The materials and methods used were an Intel Core i7 10 Th Gen laptop, Chem Office Professional 17.1, Chem 2D, Chem 3D software, PDB code (6W9K) and ligand (TUA), Stigmastan-3,6 dione (C29H48O2) from the EtOAc fraction of fruit M. charantia L was docked using MVD software, RMSD and RMSF values ​​were viewed using Yasara Software, pkCSM online tool to predict compound toxicity, toxicity prediction (LD50) was used by Protox online tool. The results of molecular docking of standard compounds, namely Methylprednisolone and Prednisolone and Stigmastan-3,6-dione, have Rerank Score values of -120.62, -121.47, -79.50, respectively. The lower the Rerank score value, the lower the binding energy between the protein and the ligand, causing the protein and ligand bonds to be more stable and it is predicted that the activity of the compound will be greater. The movement of RMSD values ​​between 0.6-1.9 Å for the 3 (three) compounds, is still within stable limits and does not undergo conformation. The RMSF value of the 3 (three) compounds has the same amino acid residue pattern. The insilico toxicity prediction for the 3 (three) compounds is still within safe limits. The EtOAc fraction of M. charantia L fruit with the active compound Stigmastan-3,6-Dione in its mechanism of action in silico shows activity as an anti-inflammatory and immunostimulant that works on the NF-kB pathway.